PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI MENGGUNAKAN POWTOON UNTUK MENINGKATKAN KEMAMPUAN HOTS - Nurmaharani, Rizky; Yuhana, Yuyu; Pribadi, Reksa Adya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
The aim of this research is to determine the feasibility of learning animation videos using powtoon in improving HOTS abilities at SD Negeri Rawu Serang and to determine students' high-level thinking abilities (HOTS) after learning using powtoon in class V. The research was carried out using research and development methods using 5 steps according to ADDIE consisting of Analysis, Design, Development, Implementation and Evaluation. The data analysis techniques in this research are validation questionnaires, pretest and posttest. Based on the results of the feasibility test analysis, validation from all expert teams obtained a score of 87.25. The results of students' mastery of the development of HOTS-based Powtoon learning video learning media are through two stages using pretest and posttest. Learning activities with pretest results obtained were 54.3. After students learn using Powtoon media, students' grades increase. After taking the Posttest, a percentage was obtained with a score of 92.3. Therefore, it is concluded that animated learning video media using Powtoon can improve students' ability to think at a higher level or higher order thinking skills (HOTS).